A Comparison of the Labor Progression Pattern with Friedman\'s Labor Curve in Nulliparous Women, Fasa, Iran - N Mohammad Salehi; HR Tabatabaee; M Raoofi; A Mohammad Beigi (Tehran University of Medical Sciences, 2009)
Background & Aim: Labor refers to a chain of physiologic events that allows a fetus to undertake its journey from the uterus to the outside. Friedman (1954) described a sigmoid pattern for labor. This study was carried out to compare the pattern of labor progression in nullipara women of Fasa with the Friedman;aposs labor curve. Methods & Materials: This cross-sectional study was conducted among 619 nulliparous women aged 18-35 who had term delivery and had no serious disease. In order to data analysis, we used one way ANOVA for comparing the means, and fixed effect of regression models in reverse method for curves drawings. Results: In all of the subgroups, effacement rate increased by increasing the cervical dilatation. Mean of dilatation rate was significantly higher in induced group than the other groups. Duration of the active phase was longer in the group that had sedation than the other two groups. Means of the duration of active phase and second stage were significantly lower in our study than the durations in the Freidman;aposs study (P<0.001) (3.87 hours vs. 4.9 hours and 52 minutes vs. 57 minutes, respectively). We did not observe the deceleration phase in our study. Conclusion: The pattern of labor progression differed from the Freidman;aposs curve and had not sigmoid shape. The most important factor in latent phase was the time of admission to the labor ward.